Air column beside the trachea. (3rd March 2016) - Hadda, Vijay; Kumar, Rohit; Madan, Karan; Mohan, Anant
Abstract : A 60-year-old man, a non-smoker, was referred to us for evaluation of an abnormal chest radiograph that had been taken 2 months earlier when the patient had fever and cough. The fever and cough had subsided after treatment with antibiotics. The patient was asymptomatic at the time of presentation to us. Examination was unremarkable. The chest radiograph showed an air pocket in the right paratracheal region. The diagnosis and differential diagnoses are discussed in this case report.